PENERAPAN STRATEGI PEMBELAJARAN ELABORASI UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA KELAS IV BIDANG STUDI FIQH DI MADRASAH IBTIDAIYAH MUHAMMADIYAH TELUK KUANTAN KABUPATEN KUANTAN SINGINGI - Ridha Radhiyah; Zulhaini Zulhaini (Universitas Islam Kuantan Singingi, 2020)
The aim of the authors in conducting research is to find out the increase in learning achievement and the factors that influence the learning achievement of Fiqh in IV.1 grade students by applying the Elaboration strategy in MI Muhammadiyah, Kuantan Bay. As the subject in this study were one Fiqh teacher and all students of class IV.1 MI Muhammadiyah Kuantan Bay, amounting to 31 people consisting of 21 male students and 10 female students, while as an object was the application of elaboration learning strategies in improving class IV.1 student achievement in Fiqh in MI Muhammadiyah Kuantan Bay Kuantan Singingi Regency. Based on the results of data collection by observation, test, interview and documentation, then analyzed the data using graphs it can be concluded that: Application of the Elaboration Strategy can improve the learning achievement of fourth grade students in the field of Fiqh in MI Muhammadiyah Kuantan Bay Kuantan Singingi Regency, this as evidenced by an increase in student learning outcomes ranging from pre Cycle to Cycle III with a percentage of 74.12 (pre Cycle), 77.00 (Cycle I), 82.51 (Cycle II) and 88.58 (Cycle III) .. The factors that influence the implementation of the Elaboration learning strategy in improving the learning achievement of fourth grade students in the field of Fiqh in Madrasah Ibtida'iyah Muhammadiyah Kuantan Bay Kuantan Singingi Regency based on observations are: Lack of strategies and techniques in Fiqh learning applied by teachers., Lack of the ability of students to understand the chart or subject matter so that they have difficulty when the percentage. And the ability of students who lack in speaking without a concept.